2014
DOI: 10.1186/bf03352080
|View full text |Cite
|
Sign up to set email alerts
|

Incessant excitation of the Earth’s free oscillations

Abstract: We, for the first time, report the evidence of incessant excitation of the Earth's free oscillations, mainly the fundamental spheroidal modes in a frequency range from 0.3 to 5 mHz, based on the three year record of a superconducting gravimeter at Syowa Station, East Antarctica. The frequency-time spectrogram of this record is striped by more than 30 lines at nGal level parallel to the time axis, mostly corresponding to the fundamental spheroidal modes. This spectrogram is characterized by relatively efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 12 publications
2
86
0
Order By: Relevance
“…1. Analysis of vertical seismometer records by Lin'kov et al (1982aLin'kov et al ( , 1989 and that of superconducting gravimeter records by Nawa et al (1998) have shown that the 0 S 2 oscillation is observed not only after very large earthquakes, but also on seismically quiet days. The penetration of the 0 S 2 oscillation into the atmosphere is demonstrated by (i) microbarograph observations of 0 S 2 multiplet components in the spectra of ground pressure variations (Garmash et al, 1989), (ii) synchronous, co-located microbarograph and seismograph observations of a certain phase relationship for 0 S 2 components , and (iii) the observation of all five 0 S 2 components in the spectrum of the geomagnetic AE-index (Bobova et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Analysis of vertical seismometer records by Lin'kov et al (1982aLin'kov et al ( , 1989 and that of superconducting gravimeter records by Nawa et al (1998) have shown that the 0 S 2 oscillation is observed not only after very large earthquakes, but also on seismically quiet days. The penetration of the 0 S 2 oscillation into the atmosphere is demonstrated by (i) microbarograph observations of 0 S 2 multiplet components in the spectra of ground pressure variations (Garmash et al, 1989), (ii) synchronous, co-located microbarograph and seismograph observations of a certain phase relationship for 0 S 2 components , and (iii) the observation of all five 0 S 2 components in the spectrum of the geomagnetic AE-index (Bobova et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the SG spectrograms show the oscillations of unknown origin in the frequency range of interest. For example, the SG spectrograms of Nawa et al (1998) for stations in Antarctica, Japan, and Australia show peaks at about 0.25 and 0.35 mHz. These peaks can be correlated with some oscillations in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…This minimum in the vertical PSD and the difference between vertical and horizontal noise at these frequencies is nicely explained by the contributions from the atmosphere as described in detail by Zürn and Wielandt (2007) and . This special feature in the vertical noise PSD allows the clear detection of the Earth's background free oscillations ("Hum") in the vertical component records of many stations (e. g. Nawa et al, 1998;Suda et al 1998;Tanimoto et al 1998;Nishida et al 2002;Ekström, 2001;Fukao et al, 2002;Rhie and Romanowicz, 2004;Kurrle and Widmer-Schnidrig, 2006), while in contrast the horizontal hum can only be detected at barely a handful of them (Kurrle and Widmer-Schnidrig, 2008). Zürn and Wielandt (2007) were not able to directly demonstrate the reversal in the sign of the pressure admittance for vertical acceleration in real records.…”
Section: Introductionmentioning
confidence: 99%
“…The Earth's free spheroidal oscillations of 0 S 2 , 2 S 1 , and 0 S 3 fall in the high-frequency part of this period region (e.g., Rosat et al, 2005). The Earth's free oscillations are shown to occur not only after large earthquakes, but also on seismically quiet days (e.g., Lin'kov et al, 1991;Davydov and Dolgikh, 1997;Nawa et al, 1998). Measurements of surfacepressure variation have revealed the penetration the 0 S 2 oscillation at a period of 54 min (309 µHz) to the atmosphere even on seismically quiet days (Garmash et al, 1989;Lin'kov et al, 1991;Shved et al, 2000).…”
Section: Discussionmentioning
confidence: 99%